Reflections on "thinking postfeminism transnationally". Issue 8 (17th November 2021) - Dosekun, Simidele
ABSTRACT: This brief piece looks back to and forward from the 2015 article published in this journal, "For Western Girls Only? Postfeminism as Transnational Culture." I reflect on how the concept of postfeminism as "transnational culture" has been taken up by other feminist media and cultural scholars, and also where, that is to say, questioning where the "transnational" is considered to be.